1988
DOI: 10.1209/0295-5075/7/3/009
|View full text |Cite
|
Sign up to set email alerts
|

Stability of the Steady-State-Stimulated Brillouin Scattering

Abstract: It is discussed whether steady-state-stimulated Brillouin scattering (SBS) can exist in homogeneous plasmas. For the case when the damping of the ion-sound waves is more important than their convection, the general solutions of the associated perturbed equations are presented and the influence of various boundary conditions is discussed. Steady-state SBS in semi-infinite plasmas is nearly always unstable. The same is true for SBS with reflective boundary conditions, although the physical mechanism is different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1989
1989
2002
2002

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…This has not yet been done. For no temporal dephasing (A = 0), Blaha et aL [3] showed that this fourth order system reduces to two second order equations, one each for the real and imaginary parts. These second order equations can then each be transformed into Legendre equations and the time evolution of perturbations can be found in terms of associated Legendre functions.…”
Section: (10)mentioning
confidence: 99%
See 1 more Smart Citation
“…This has not yet been done. For no temporal dephasing (A = 0), Blaha et aL [3] showed that this fourth order system reduces to two second order equations, one each for the real and imaginary parts. These second order equations can then each be transformed into Legendre equations and the time evolution of perturbations can be found in terms of associated Legendre functions.…”
Section: (10)mentioning
confidence: 99%
“…The dynamics of Stimulated Brillouin Scattering (SBS) in a homogeneous finite medium has captured considerable interest both in laser-plasma interactions [1][2][3][4] and in optical fibers [5][6][7][8][9][10]. SBS is a three wave interaction (3WI) that results from a parametric coupling between electromagnetic (light) and acoustic waves.…”
Section: Introductionmentioning
confidence: 99%